Public-Private Partnerships for Innovation and Sustainability Transformation: An Embedded, Comparative Case Study of Municipal Waste Management in England And Denmark - Sofie Dam (Copenhagen Business School (CBS), 2015)
This PhD concerns the potentials and challenges for conducting innovation in public-private partnerships (PPPs) towards the objective of transforming municipal waste management towards more sustainable systems. In recent years, local authorities have been met with intensified demands from the EU and national governments to change existing waste management systems from solutions based on disposal and recovery towards more recycling and prevention and at the same time deliver more efficient waste management services through the inclusion of private businesses. These two demands may to some degree be mutually supportive, but may also lead to challenges in the prioritization and development of new solutions.
hdl:10398/9169
Keywords: 650